Effect of an adaptive career-consultation mobile application on students' competency development. (2017) - Wu, Po-Han; Huang, Yu-Hsien
Graduate youth unemployment has recently substantially increased, and the learning-application gap is a major problem. Universities are crucial for addressing this gap. An adaptive career-consultation mobile application (ACCMA) integrating student capabilities and interests was developed to help students connect what they are learning at university with workplace needs. With a questionnaire, 475 senior university students were surveyed. The ACCMA was significantly more beneficial than general career counselling at assisting students in understanding their capabilities and interests and planning their future careers. Additionally, students were more satisfied with this method of career consultation. It is suggested that the learning-application gap can be reduced by using mobile technology to provide students with information and by assessing students' capabilities and interests, and how they may fit in the current employment market. This will enhance their employability and competitiveness and reinforce their future career development.